TYPES OF SYNTACTIC RELATIONS IN A SENTENCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of the main types of syntactic relations in sentences, a key topic in syntactic analysis within linguistics. It explores how words and phrases are organized and connected to convey meaning, covering coordination, subordination, modification, predication, complementation, and agreement. Each section defines a syntactic relation, provides examples, and explains how that relation contributes to sentence structure and meaning. The article emphasizes the importance of understanding these relationships for analyzing language mechanics, improving grammatical accuracy, and enhancing communication skills. It is a useful resource for students of linguistics, writers, and anyone interested in deepening their understanding of sentence structure and syntax.